Innovation with Information Technologies and Using Nostalgia as an Organizational Strategy - Mojdeh Pajoutan; Chad Seifried (Journal of Applied Sports Management, 2014)
The purpose of this paper is to show how sport organizations can use innovation through information technology (IT) to support the pursuit of nostalgia by revenue-oriented sport organizations as an organizational strategy to improve or maintain their fan nation. Collectively, a five-stage flowchart is offered that demonstrates an innovation process using IT for nostalgia to improve the placement of sport organizations in competitive markets. The foundation for this work’s approach is based on expanding Damanpour and Schneider’s (2006) three stages of innovation process in organizations, which include 1) initiation, 2) adoption decision, and 3) implementation. Wolfe’s (1994) “process of innovation” or the “temporal sequence of activities” that organizations go through to implement innovations is also represented in the developed flowchart discussion (Wolfe, 1994; p. 409). Finally, potential future research directions are suggested for scholars and practioners to consider with respect to IT, innovation, and nostalgia.
Keywords: innovation; nostalgia; information technology